Cohesion in cycling neo-tribes: a netnographic approach. Issue 3 (4th May 2022) - Asan, Kubra; Chi, Christina Geng-qing; Yolal, Medet
ABSTRACT: People come together and create new communities around their special interests. Although the members of these communities, defined as neo-tribes, have highly individualistic, fluid and reflexive identities, they share 'an intense sense of us', in other words, cohesion. This study presents a netnographic examination of two different cycling communities in Turkey to explain the concept of cohesion in neo-tribes. The results of the study indicate that the neo-tribe members express their cohesion under the themes of acting together, entertaining together, collaboration, appreciation, shared values and shared concerns. This study allows for a better understanding of the cycling community and provides important insights to developing cycling for leisure, recreation and tourism purposes.